Import market penetration in services - Rolf J. Langhammer (Intereconomics, 1991)
The EC-1992 programme foresees the complete liberalization of trade in services among member countries. To what extent has import market penetration in the Community already begun in selected service industries? Which EC member countries have been the forerunners to date? The following paper uses a new data base released recently by EUROSTAT in an attempt to answer these and other related questions.
Keywords: 330; Internationaler Dienstleistungsverkehr; EU-Binnenmarkt; EU-Staaten